HaNDL syndrome in a 14-year-old girl - Rivero-Sanz, Elena (BMJ Case Rep, 2016)
Transient headache and neurological deficits with cerebrospinal fluid lymphocytosis (HaNDL syndrome) consists of recurrent headaches with focal neurological signs, which can include motor, sensory and aphasic symptoms. Although considered rare, it is becoming increasingly recognised in clinical practice due to the accumulation of case reports. The pathophysiology remains unclear although changes in the neurovascular resemble those found in migraine, which are thought to be triggered by an infectious process. HaNDL can mimic various serious, including life-threatening, diseases, such as stroke and meningoencephalitis, which is why vigorous tests should be sought before this diagnosis of exclusion can be reached. Treatment is symptomatic and the prognosis is excellent. A literature review of the topic is discussed. We report an adolescent girl who presented with recurrent expressive dysphasia and right-sided hypoaesthesia and moderate occipital headaches who was diagnosed with HaNDL syndrome.